Immobilized Cu(I) on Organic-Inorganic Hybrid Material: An Effective and Reusable Catalyst for Biginelli Reaction - L. Zhang, Xiao; Wang, Min; Wang, Lei (Letters in Organic Chemistry, 2011)
The immobilized Cu(I) on organic-inorganic hybrid material was prepared and used as effective catalyst for the Biginelli reaction. In the presence of immobilized copper catalyst, aromatic aldehydes reacted with β-keto ester and urea (or thiourea) smoothly to generate the corresponding Biginelli products in good to excellent yields without any additive. The work-up procedure is very simple and practical. Furthermore, the silica-supported Cu(I) could be recovered and recycled for eight consecutive trials without significant loss of its reactivity.
Keywords: Immobilization of Cu(I)